Effect of Distillery Effluent on Some Agricultural Crops, A Case of Environmental Injustice to Local Farmers in Khajura VDC, Banke - Ale, Rita; Jha, PK; Belbase, N (Scientific World, 2010)
Effluent discharged from the Karnali distillery Pvt. Ltd was analyzed to measure its effect on agricultural crops and environmental justice to the concerned people. Physico-chemical parameters like pH, temperature, Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Particles (TSS), Nitrogen (N), Phosphorus (P), Potassium (K) and some heavy metals such as Iron (Fe), Manganese (Mn), Cadmium (Cd), Lead (Pb), Zinc (Zn), and Copper (Cu) were analyzed and found most of the physico-chemical parameters were above the toxic level set by Nepal Bureau Standard. The analysis of physico-chemical parameters of the soil irrigated with effluent polluted water revealed appreciable increase in the soil nutrients (Organic Matter, N, P, K) along with the increase of toxic heavy metals such as Fe, Cd, Mn and Pb in the soil which has decreased annual crop productivity by around 40 percent. Similarly the effect of the effluent on seed germination, seedling growth, fresh weight and dry weight of seedlings of two test crops (Oryza sativa and Triticum aestivum) were also analyzed and found the effect varied in different concentration of treatment. Higher concentrations (10%, 25%) were found completely inhibitory where as lower concentrations (1%, 5%) were found stimulatory and reached up to the level of control. The present study showed that the distillery effluent was highly loaded with organic pollutants along with harmful heavy metals which showed significant effect on soil quality and the crop productivity which caused environmental injustice to the local people in terms of loss of crop productivity and environmental hazards. Key words: Heavy metals; Effluent; Pollution; Soil chemistry; Environmental justice. DOI: 10.3126/sw.v6i6.2637 Scientific World, Vol. 6, No. 6, July 2008 68-75